Repeatability of dynamic 3D phase‐resolved functional lung (PREFUL) ventilation MR Imaging in patients with chronic obstructive pulmonary disease and healthy volunteers. Issue 2 (9th February 2021) - Klimeš, Filip; Voskrebenzev, Andreas; Gutberlet, Marcel; Obert, Arnd J.; Pöhler, Gesa H.; Grimm, Robert; Behrendt, Lea; Crisosto, Cristian; Glandorf, Julian; Moher Alsady, Tawfik; Wacker, Frank; Vogel‐Claussen, Jens
Abstract : Background: A previous study has demonstrated the feasibility of 3D phase‐resolved functional lung (PREFUL) MRI in healthy volunteers and patients with chronic pulmonary disease. Before clinical use, the repeatability of the ventilation parameters derived from 3D PREFUL MRI must be determined. Purpose: To evaluate repeatability of 3D PREFUL and to compare with pulmonary functional lung testing (PFT). Study Type: Prospective. Population: Fifty‐three healthy subjects and 13 patients with chronic obstructive pulmonary disease (COPD). Field Strength/Sequence: A prototype 3D stack‐of‐stars spoiled‐gradient‐echo sequence at 1.5 T. Assessment: Study participants underwent repeated MRI examination (median time interval between scans COPD/healthy subjects [interquartile range]: 7/0 days [6–8/0–0 days]) and one PFT carried out at the time of the baseline MRI. For 3D PREFUL, regional ventilation (RVent) and flow‐volume loops were computed and rated by cross‐correlation (CC). Also, ventilation time‐to‐peak (VTTP) was computed. Ventilation defect percentage (VDP) maps were obtained for RVent and CC. Statistical Tests: Repeatability of 3D PREFUL parameters was evaluated using Bland–Altman analysis, coefficient of variation (COV) and intraclass correlation coefficient (ICC). The relation between 3D PREFUL and PFT measures (forced expiratory volume in 1 second (FEV1 ) and forced vital capacity (FVC) was assessed using the Pearson correlation coefficient ( r ). Results: In healthy subjects and COPD patients, no significant bias (all P range: 0.09–0.77) and a moderate to good repeatability of RVent, VTTP, and VDPRVent were found (COV range: 0.1%–18.2%, ICC range: 0.51–0.88). For CC and VDPCC moderate repeatability was found (COV range: 0.6%–43.6%, ICC: 0.38–0.60). CC, VDPRVent, and VDPCC showed a good correlation with FEV1 (all | r | > 0.58, all P < 0.05) and FEV1 /FVC ratio (all | r | > 0.62, all P < 0.05). Data Conclusion: 3D PREFUL provided a good repeatability of RVent, VTTP, and VDPRVent and moderate repeatability of CC and VDPCC in healthy volunteers and COPD patients, and correlated well with FEV1 and FEV1 /FVC. Level of Evidence: 2 Technical Efficacy Stage: 2